Data from: Climatic niche differences between diploid and tetraploid cytotypes of Chamerion angustifolium (Onagraceae) - Thompson, Ken A.; Husband, Brian C.; Maherali, Hafiz (Zenodo, 2015)
Premise of the study: Polyploidy—the possession of more than two copies of each chromosome in the nucleus—is common in flowering plants. Polyploid plants can occupy different geographic ranges than their diploid progenitors, but the factors responsible for maintaining these range differences are poorly understood. Polyploidy can have significant physiological consequences, and the present study aims to determine whether previously described physiological differences between cytotypes are correlated with climatic niches and geographic distributions. Methods: Prior research indicates that tetraploid Chamerion angustifolium (Onagraceae) are more tolerant of drought and less tolerant of freezing than diploids, which suggests that they should occupy a niche that is warmer and drier than that of diploids. We extracted climate data for 134 C. angustifolium populations classified as pure diploid, pure tetraploid, or mixed-ploidy. We compared climatic conditions between these population categories, and generated ecological niche models to compare their geographic distribution with prior qualitative estimates. Key results: Pure tetraploid populations occupy habitats that are warmer and drier than pure diploid populations. Mixed-ploidy populations occur in habitats that are not strictly intermediate between pure diploid and pure tetraploid populations, but are as cold as pure diploid populations and have intermediate soil moisture deficits. Our niche models were similar to previous qualitative estimates of cytotype geographic distribution. Conclusions: The correspondence between the physiological tolerances of cytotypes, their climatic niches, and their geographic distributions suggests that physiological traits are at least partially responsible for differences in the realized climatic niches of diploid and tetraploid C. angustifolium. ChamerionPopulationData Population information for 134 populations of Chamerion angustifolium sampled across North America, Greenland, Iceland. Includes Lat/Long, Ploidy (Diploid, ...